(untitled) (INTEGRATION PROCEEDING, 2023)
This is a conceptional article which the writer proposes a concept of using Tik Tok application to improve students’ speaking skill in English language teaching. In today’s era, technology is advancing and developing. Actually, there are many applications that can be used as a learning media in teaching and learning process. One of applications that can be used is the Tik Tok Application. In learning English, speaking is one of the skills that has to be mastered by the students. Therefore, the teacher needs the media that help the students to have good speaking skill. Hypothetically, Tik Tok Application can improve speaking skill. The teacher can ask the students to create story telling videos by using Tik Tok Application. Thus, it is not only improving the students’ confidence to speak up but also the creativeness of the students. In conclusion, Tik Tok application is one of alternative media that can be used in learning speaking skill.